New approaches to quantitative evaluation of international economic relations - Шабалтас, А. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The paper considers the main approaches to the quantitative assessment of international economic relations. Overview and most effective methods available, including: multiple linear regression, correlation, gravity model. Of particular importance given model checking on the adequacy and efficiency.The possibilities of the use of models in contemporary research on the world economy and international economic relations based on macroeconomic features of the post-Soviet space.